Efficacy and Stability studies of microbial folate fortified fruit juices prepared using probiotic microorganism - Deep, S.; Ojha, S.; Kundu, S. (Cellular and Molecular Biology, 2017)
Folate, natural form of water soluble vitamin folic acid, is significant for humans as involved in most important metabolic reactions i.e. nucleotide synthesis and amino acid inter conversions. Thus its deficiency causes neural tube defects in newborns and cardiovascular diseases, and cancers. Humans cannot synthesize folate de novo so consumption through diet is essential. Natural food sources, supplements and fortified food products are the choices available to complete the Daily recommended intake. However microbial fortification using probiotics recently gained wide attention due to dual advantage of natural food matrix with enhanced folate content along with the probiotics benefits. Current study was focused on the microbial fortification of fruit juices and their efficacy and stability studies. Freshly filtered orange and tomato juice was prepared and inoculated with Streptococcus thermophilus NCIM 2904. Incubation was done at 40°C and samples were collected at different time interval. Folate extraction was done using human plasma and content was measured by microbiological assay using Lactobacillus casei NCIM No. 2364. Efficacy and stability studies were carried out to ensure the quality of juices to be consumed in terms of folate content, viable cell count and pH after 4 weeks of storage at low temperature. Positive results were observed as folate content was quite stable whereas viable cell count was also found to be significant till some time without adding any preservatives. The results indicated that fortified fruit juices could be used as probiotic beverages with enhanced folate content.